Use of Insulin Degludec/Insulin Aspart in the Management of Diabetes Mellitus: Expert Panel Recommendations on Appropriate Practice Patterns - YAVUZ, DİLEK; DEMİRCİOĞLU, SERAP (FRONTIERS MEDIA SA, 2021)
Insulin degludec/insulin aspart (IDegAsp) is a fixed-ratio co-formulation of insulin degludec (IDeg), which provides long-lasting basal insulin coverage, and insulin aspart (IAsp), which targets post-prandial glucose. This expert panel aimed to provide a practical and implementable guidance document to assist clinicians in prescribing IDegAsp in the diabetes management with respect to different patient populations including children and adults with type 1 diabetes (T1D) or type 2 diabetes (T2D) as well as pregnant, elderly and hospitalized patients and varying practice patterns (insulin-naive, insulin-treated, switching from basal, basal bolus and premix regimens). The experts recommended that IDegAsp can be used in insulin-naive T2D patients with poor glycemic control (HbA1c >8.5%) despite optimal oral antidiabetic drugs (OADs) as well as in insulin-treated T2D patients by switching from basal insulin, basal-bolus therapy or premixed insulins in relation to lower risk of nocturnal hypoglycemia, fewer injections and lower intraday glycemic variability, respectively. The experts considered the use of IDegAsp in children with T2D as a basal bolus alternative rather than as an alternative to basal insulin after metformin failure, use of IDegAsp in adult T1D patients as a simplified basal bolus regimen with lesser nocturnal hypoglycemia, fewer injections and better fasting plasma glucose control and in children with T1D as an alternative insulin regimen with fewer injection to increase treatment adherence. The proposed expert opinion provides practical information on use of IDegAsp in different patient populations and practice patterns to assist clinicians, which seems to compensate the need for easily implementable guidance on this novel insulin regimen.
Keywords: expert panel; type 2 diabetes; type 1 diabetes; glycemic control; hypoglycemia; Turkey; IDegAsp; treatment switching